Evacuatory Dysfunction after Stapled Hemorrhoidopexy: A Case Report of Rectal Pocket Syndrome - Maejima, Taku (J Anus Rectum Colon, 2020)
A 60 year-old male was referred to the authors' hospital with a persistent urge to defecate. The patient had undergone stapled hemorrhoidopexy (SH) for the treatment of prolapsed hemorrhoids approximately 10 years earlier. He started to have difficulty with defecation and a false sense of urgency shortly after the surgery. Computed tomography showed a diverticulum-like fistula along the circumference of the rectum. Colonoscopy revealed communication between the diverticular cavity and the rectal lumen. The cavity contained a thumbnail-sized fecalith. When the fecalith was removed, the patient's urge to defecate dissipated. The patient was diagnosed with rectal pocket syndrome secondary to SH. The lower rectum was transected, and the remaining rectum and the anal canal were anastomosed by manual suture. Temporary ileostomy with double orifices was performed. The ileostomy was closed 3 months later. The patient experienced no subsequent difficulty with defecation or urgency.